PENGEMBANGAN APLIKASI SEWA MOBIL YANG MEMBAWA PILI HAN DAN KENYAMANAN BAGI PELANGGAN: DEVELOPMENT OF A CAR RENTAL APP THAT BRINGS PILI HAN AND CONVENIENCE TO CUSTOMERS - Muh Dzaky Baridwan; Dimas Prayoga; Akmar Aqilah Kautsar; Andi Fatir Islam; Putri Nirmala; Fadhlirrahman Baso (CV. Sakura Digital Nusantara, 2025)
The development of means of transport is now increasing rapidly, making it easier and more efficient for people. Transport is not only a means of moving places, but also contributes to economic, social and quality of life activities. This research uses the agile method for the development of the Drift Rent car rental application. The agile method is an approach that focuses on incremental and iterative system development, prioritising teamwork between developers and customers and the ability to adapt to changes during the development process. The development of the Drift Rent app began with the analysis phase, where the car rental app was identified as a user and business need. This analysis included data collection through surveys and interviews with potential users, as well as a review of similar applications. The results of the analysis showed that users needed an application that facilitated login, registration, booking a car, and viewing order history. Based on the development of this project, it can be concluded that the car rental app successfully combines the required features with a user-friendly interface. All business objectives and user needs have been considered in the development process, from analysis to testing. Through this application, users can easily login, book a car, and view their order history.